Estudio de la eficacia de cuatro métodos de inoculación artificial con aspergillus flavus link Ex fries en seis genotipos de maíz (Zea Mays L) bajo condición de campo. (ING) - Quesada, Miguel (1986)
Four different inoculation methods were tested on six corn genotypes, under field condition. In call cases 1ml. Of 5 x 105 conidial suspension was applied, as follows: injection with a hypodermic needle in the central part of the ear (M1), injection in the silk channel (M2),  inoculum deposition on a wonded section of the ear (M3), inoculum deposition on the ear silk (M4). According to the statistical analysis the most efficient method was M3, followed by M1, M4 and M2. Fusarium spp and A. flavus showed a significative negative correlation (p>0,01) among them. Methods where inoculum was placed on the upper part of the ear showed more Fusarium and other fungi competition with A. flavus, and less efficiency. No statistical differences was found among genotypes.